Mengenal Lebih Dekat Dampak Aktivitas Work from Home (WFH) dan Neck Pain di Masa Pandemi - Khairunnisa, Salwa; Ghifari Rifansha, Muhammad; Rizky Lestari, Ayundha; Nabila, Cahya (Jurnal Syntax Fusion, 2021)
Since the pandemic, all countries have implemented Work From Home (WFH) policies, which are new policies that utilize the virtual world. As for the negative effects that can be given from WFH, such as the occurrence of Neck Pain. Neck Pain is pain in the cervical spine from the superior line of the first thoracic spinous nuchal process. Reported cases of neck pain in office workers as much as 15% to 34.4%. Source searches were carried out on the online portal of journal publications as many as 27 sources from Medscape, Google Scholar, National Center for Biotechnology Information (NCBI) with the keywords WFH and Neck Pain. Sitting in a chair or bed without a table while working on a computer or laptop can cause neck pain and the upper or lower back area. When fatigue occurs in the neck muscles, it can cause static muscle contractions that last a long time, if this condition occurs continuously there will be pain and discomfort in the neck muscle area which can eventually lead to disability. In this study, the author uses a qualitative method with a literature review research paradigm. Qualitative research methods are carried out in natural conditions and carried out on direct data sources. The purpose of the qualitative method is to gain an understanding of the meaning of the problem to be studied.